The anticancer efficiency of the xenogeneic vaccine and the indication for its use - Symchych, T.V.; Fedosova, N.I.; Karaman, O.M.; Yevstratieva, L.M.; Lisovenko, H.S.; Voyeykova, I.M.; Potebnia, H.P. (Experimental Oncology, 2014)
Aim: To investigate the anticancer efficiency of the xenogeneic vaccine in different tumor models and to assess the possibility whether level of antibodies (Ab) specific for vaccine’s proteins can be used as an indication for its use. Methods: Mice with Lewis lung carcinoma (LLC), Ehrlich carcinoma (EC) or Sarcoma 37 (S37) were immunized with a xenogeneic anticancer vaccine based on chicken embryo proteins (CEP) and its anticancer activity was examined. The level of specific Ab in the blood serum of non-immunized tumor-bearing mice was studied by ELISA. Results: CEP application statically significantly inhibited the growth of LLC (the index of tumor growth inhibition was 42.10–53.13% depending on the day of tumor growth); vaccinated mice with EC showed significant tumor growth inhibition and life prolongation by 34.48%. Among mice with S37, there was noticed no antitumor effect. The number of tumor-bearing non-immunized mice which have had pre-existing CEP-specific Ab did not differ depending on the tumor model. The level of CEP-specific Ab among mice with LLC and EC increased with the growth of the tumor volume, but it decreased among mice bearing S37. Probably, the low level of CEP-specific Ab alongside huge tumor burden shows it is futile to apply the CEP-based vaccine. Conclusion: Different tumor strains vary in their susceptibility to CEP-based vaccine. Probably, the low level of CEP-specific Ab when a tumor burden is huge shows it is futile to apply the CEP-based vaccine. Key Words: xenogeneic anticancer vaccine, chicken embryo proteins anticancer activity, Lewis lung carcinoma, Ehrlich carcinoma, Sarcoma 37, CEP-specific antibodies. Key Words: xenogeneic anticancer vaccine, chicken embryo proteins anticancer activity, Lewis lung carcinoma, Ehrlich carcinoma, Sarcoma 37, CEP-specific antibodies.